Two-dimensional ultrafast vibrational spectroscopy of azides in ionic liquids reveals solute-specific solvation. Issue 40 (21st July 2015) - Dutta, Samrat; Ren, Zhe; Brinzer, Thomas; Garrett-Roe, Sean
Abstract : 2D-IR studies of organic and inorganic azides dissolved in ionic liquids show different solvation structures and picosecond dynamics. Abstract : The stereochemistry and the reaction rates of bimolecular nucleophilic substitution reactions involving azides in ionic liquids are governed by solute–solvent interactions. Two-dimensional ultrafast vibrational spectroscopy (2D-IR) shows that the picosecond dynamics of inorganic azides are substantially slower than organic azides in a series of homologous imidazolium ionic liquids. In water, both organic and inorganic azides spectrally diffuse with a ∼2 ps time constant. In the aprotic solvent tetrahydrofuran, both kinds of azides spectrally diffuse on a timescale >5 ps. In ionic liquids, like 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM][BF4 ]), organic azides spectrally diffuse with a 2–4 ps time constant, and inorganic azides spectrally diffuse with a >40 ps time constant. Such a striking difference suggests that neutral (organic) and charged (inorganic) azides are incorporated in the ionic liquids with different solvation structures.